Animal stories - Namm, Diane; Freeberg, Eric (New York : Sterling, 2010)
An abridged retelling of a dozen stories about animals from well-known authors.
"Just so" stories / by Rudyard Kipling. How the elephant got his trunk ; How the camel got his hump ; How the rhinoceros got his skin ; How the leopard got his spots ; How the whale got his throat ; The beginning of the armadillos -- Stories by Hans Christian Andersen. The leap-frog ; The wild swans -- Dog stories. A dog's tale / by Mark Twain ; Brown wolf / by Jack London -- Stories from "Queer Little Folks" / by Harriet Beecher Stowe. The squirrels that live in a house ; Mother Magpie's mischief.
4.5
3-6
3-6
Keywords: Animals -- Juvenile fiction; Animals -- Fiction; Short stories; Animals -- Fiction; Short stories; Short stories